Primary Cutaneous Aspergillosis in an Immunocompetent Patient: A Case Report from a Tertiary Care Hospital in Chennai - Ravichandran, Sathyakamala; Shanmugam, Priyadarshini; Thayikkannu, Ambujavalli Balakrishnan; Elangovan, Pradeep (Journal of Laboratory Physicians, 2022)
Aspergillosis is a systemic fungal infection that commonly affects immunocompromised individuals and, less frequently, immunocompetent individuals. It is the most common opportunistic fungal disease after candidiasis. This is primarily a pulmonary infection and can also involve other body sites like paranasal sinuses and cutaneous tissues. Aspergillus fumigatus, Aspergillus niger, and Aspergillus flavus are the common species infecting humans. Primary cutaneous aspergillosis (PCA) is usually caused by A. flavus and A. fumigatus. It is commonly seen in immunocompromised patients such as those suffering from diabetes, malignancies, tuberculosis, human immunodeficiency virus, or patients on long-term steroids and antibiotics. In this article, we report a case of PCA, in the immediate postoperative period, following a road traffic accident, in an immunocompetent patient. This posed a diagnostic challenge to the treating physicians. A. flavus was confirmed with 10% potassium hydroxide mount, lactophenol cotton blue, and growth on Sabouraud dextrose agar from tissue culture sample. Antifungal treatment was initiated with oral itraconazole 200 mg after performing antifungal susceptibility testing based on Clinical and Laboratory Standards Institute guidelines. The patient's condition improved and was discharged. Thus, early detection of PCA combined with medical and surgical intervention can successfully eradicate infection and help in preventing disseminated aspergillosis.
Keywords: Aspergillus flavus; immunocompetent; primary cutaneous aspergillosis; systemic fungal infection